DECISION SUPPORT SYSTEM FOR "BULELENG CERDAS" PROGRAM SOCIAL FUND RECIPIENT CANDIDATES WITH ANALYTICAL HIERARCHY PROCESS (AHP) AND SIMPLE ADDITIVE WEIGHTING (SAW) METHOD - Fitri, Aini Aidilah; Pradnyana, I Made Ardwi; Darmawiguna, I Gede Mahendra (Scientific Journal of Informatics, 2018)
BAZNAS in Buleleng Regency has a problem program "Buleleng Cerdas". The problems are to make a decision to choose prospective scholarship recipients. The program activities include Student Assistance, One Family One Scholar, and Student Assistance with Achievement. The problems that arise because the selection of the prospective recipients are still manual and the assessment of the final results obtained is relatively long, still difficult to identify prospective recipients who are eligible in accordance with the existing quota, because the candidates Scholarship recipients are spread in the Buleleng region for private and public schools. The purpose of this research is to develop a Decision Support System for "Buleleng Cerdas" Program Social fund Recipient Candidates with AHP and SAW Method and to know the responsiveness of users. This system is supported by a method of decision making, namely the AHP method which is used to find the weights in each criterion, and the ranking calculation with the SAW method. For the testing process, four test process stages are performed: (1) black box test, (2) white box test  (3) test UEQ percentage is positive impression & SUS percentage is 93%, (4) suitability testing of manual calculations on the system is appropriate.